Inversion polymorphisms and natural selection in Trimerotropis pallidipennis (Orthoptera) - Colombo, P.C. (2003)
Grasshoppers have been much less studied than Drosophila when it comes to inversion polymorphisms, despite the occurrence of this rearrangement in several species of grasshoppers. In the present study, 354 males from a natural population of the New World species Trimerotropis pallidipennis, polymorphic for 6 pericentric inversions in 4 chromosome pairs, were sampled at the beginning and at the end of the adult life span. This sampling, along with the fact that generations in this grasshopper are annual and discrete, was done to detect differential adult male longevity among karyotypes and departures from formal null models, such as gametic phase equilibrium. These methods allow the detection of natural selection taking place in the wild. The comparison between age classes showed that some inversions were significantly more frequent in one sample, thus revealing the operation of natural selection. Gametic phase disequilibrium was detected in the sample of aged males but not in the sample of young ones. Furthermore, here we aim to detect the phenotypic targets of longevity selection by examining morphometric characters, in order to have a clearer idea of the relation between inversions and natural selection in this species. These results corroborate previous studies that suggested that the inversions are involved in natural selection, and an adaptive model has been proposed for the pattern of inversion frequencies throughout several populations at different altitudes and latitudes.